THU0327 Comparison of Immunoenzymatic Assay and Crithidia Immunofluorescence Test for The Detection of anti-Double Strand Dna Antibodies in Patients with Systemic Lupus Erythematosus. (15th July 2016) - Orsolini, G.; Snyder, M.R.; Crowson, C.S.; Frinack, J.L.; Kevin, M.G.
Abstract : Background: Anti double strand DNA (dsDNA) antibodies are one of the immunologic hallmarks used to identify patients with systemic lupus erythematosus (SLE). However, they can be seen in patients with other connective tissue diseases (CTDs) on occasion. These auto-antibodies can also be drug-induced by medications such as anti-TNF α agents. Different methods are available for their detection. In the past, radioimmunoassays (RIA) and immunofluorescence by Crithidia (CLIFT) were commonly used. More recently, immunoenzymatic assays (ELISA) have been widely utilized. ELISA assays are much faster, cheaper and easier to perform than other methods such as CLIFT and now are the most common method used by immunology laboratories. The Crithidia test is still used in clinical practice, often for the purpose of confirmation after ELISA or further testing if ELISA is negative, but its real usefulness needs to be more clearly defined. Objectives: Investigate the relation between dsDNA Abs measured by CLIFT and ELISA. Define the clinical role for CLIFT testing. Methods: 1000 consecutive adult patients tested for anti dsDNA by ELISA in Mayo Clinic Rochester immunology lab from September to December 2015 had their sera tested also by CLIFT. Laboratory, clinical data and history were reviewed. For ELISA we used Quanta Lite dsDNA ELISA kit by Inova Diagnostic, taking as stated by the manufacturer for negative value below 30 IU/ml, for borderline between 30 and 75 IU/ml and for positive above 75 IU/ml. For CLIFT we used Crithidia Luciliae Kit by Kallestad, considering positive the samples with immunofluorescence signal from the kinetoplast or from both the kinetoplast and the nucleus. Results: CLIFT showed a very high specificity (99%) but a low sensitivity (14%) for patients with SLE. ELISA had specificity close to CLIFT (92–95%) but with a substantially better sensitivity (36–47%). ELISA performed better considering borderline as negative (positive predictive value [PPV] with borderline as negative 68% vs 63% as positive). Conclusions: CLIFT is very specific but its low sensitivity limits its usefulness. New generation ELISA has good performance, with high specificity and good sensibility. A negative test by ELISA is most of the time negative also by Crithidia, and among the rare ELISA-/CLIFT+ few patients have SLE, so there's no need to run Crithidia in ELISA negative patents. Among the ELISA positive, Crithidia could add value for some patients with SLE, but always keeping in mind the limit of sensitivity. Disclosure of Interest: None declared